Penentu Kepuasan Nelayan terhadap Program Bantuan Kerajaan di Terengganu (Jurnal Pembangunan Sosial, 2011)
Government roles, infrastructure, training, advisory service, marketing, enforcement, and research and development are important factors that can raise the life satisfaction of fishermen. The aim of this research is to identify the determinant factors of fishermen’s satisfaction towards the government aids’ programme in the state of Terengganu. This is necessary to assess whether the government policy on giving aids to the fishermen can give satisfaction and improve their quality of life. This research involved 300 respondents chosen using stratified random sampling in several fishing districts in the state of Terengganu. Data were analyzed through descriptive and inferential statistics using t-test, variance analysis, correlation and regression. The findings show that government aids contribute to the higher level of satisfaction with R2 = 0.465. While fishermen attribute contribute R2 = 0. 3 95 or 39. 5 percent of fishermen satisfaction.